FORMULASI PUDING UMBI PORANG DENGAN PENAMBAHAN TEPUNG KACANG HIJAU SEBAGAI MAKANAN SELINGAN TINGGI SERAT BAGI PENDERITA OBESITAS - Audrey Treesia Hermita Tampubolon, (2020)
Obesity is one of the major health problems that has engulf the world, including Indonesia. The increased prevalence of obesity is due to lack of fiber intake. Dietary fiber can help control and reduce the risk of obesity. Comestibles that can be utilized as a source of dietary fiber such as porang tuber and mung bean flour. This study aims to determine the effect of the best addition mung bean flour based on physical, chemical and sensory characteristics, and nutritional content (proximate) between the control formula and the selected formula. This was true experimental research with Complete Random Design (CRD). Organoleptic test analysis used the Kruskal Wallis test and continued with the Mann-Whitney test. As for the analysis of chemical and physical tests using the ANOVA test and followed by the Duncan test. Kruskal Wallis test results showed the addition of mung bean flour significantly (p <0.05) to the hedonic test of aroma parameters (p = 0.01) and taste (p = 0.051). Based on the results of the analysis of porang tuber pudding with the best addition mung bean flour, F1 formulation (25 g), contained 9,3% dietary fiber, 89.2% water, 0.33% ash, 1.77 % protein, 0.15% fat , 8.2% carbohydrate and syneresis 4.50% at 24 hours, 10.50% at 48 hours and 13.50% at 72 hours. This product is categorized as a high-fiber snack and can be used as a source of dietary fiber to prevent obesity.